PENGARUH BUDAYA ORGANISASI, LINGKUNGAN KERJA, BEBAN KERJA DAN DISIPLIN TERHADAP KINERJA GURU SMA MUHAMMADIYAH 1 GRESIK - Erni Purwanti (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2019)
This study aims to examine the influence of Organizational Culture, Work Environment, Workload and Discipline on Teacher Performance of Muhammadiyah Gresik High School. Then a literature review and hypotheses are carried out, as well as data obtained from questionnaires to 55 Muhammadiyah 1 Gresik High School Teachers using Total techniques. Sampling. Testing is done using multiple linear regression analysis. The results of the analysis show that organizational culture has a significant effect on teacher performance variables, the work environment has no effect on teacher performance variables, workload has a significant effect on teacher performance variables, discipline has a significant effect on teacher performance variables.